A highly stretchable and room temperature autonomous self-healing supramolecular organosilicon elastomer with hyperbranched structure. (5th August 2021) - Zhang, Kaiming; Wang, Zhe; Zhang, Junhao; Liu, Yuetao; Yan, Chenzhengzhe; Hu, Tongxi; Gao, Chuanhui; Wu, Yumin
Graphical abstract: Highlights: HPSi exhibits high stretchability and self-healing properties. HPSi is crosslinked by multiple reversible bonds. The energy generated by the external force is dissipated effectively by sacrificial bonds. Abstract: Preparing of polymer materials similar to biological muscle properties with highly stretchable and autonomous self-healing at room temperature is a challenge. Herein, hyperbranched organosilicon polymers (HPSi) with multiple hydrogen bonds and dynamic disulfide bonds were synthesized by amino-modified poly(dimethylsiloxane) (PDMS-NH2 ), dithiodianiline (DTDA) and thioctic acid (TA). The "free" part of hydrogen bond promoted the dynamic interaction with related complementary parts, which effectively improved the repair efficiency. As the degree of hyperbranching increased, the supramolecular branching units brought more reversible bonds to polymers. Therefore, the heal efficiency of HPSi at room temperature showed an upward trend and it could reach to 96.9%. As the sacrificial bonds, multiple reversible hydrogen bonds effectively dissipated the energy generated by external forces with the help of disulfide bonds. Thus, the stretchability of the elastomer was strengthened. And the elongation at break of elastomer was up to 3463%. This muscle-like self-healable hyperbranched elastomer with excellent mechanical properties has great application potential in the fields of soft robots, electronic devices and coatings.